2006
DOI: 10.1542/peds.2004-2699
|View full text |Cite
|
Sign up to set email alerts
|

Health, Neurologic, and Cognitive Status of HIV-Infected, Long-Surviving, and Antiretroviral-Naive Ugandan Children

Abstract: These children seem to represent a significant subgroup of HIV-infected child survivors for whom the progress of the disease is less aggressive throughout early life. Given the fact that many infants, especially in developing countries, continue to be born without the benefit of perinatal ARVT, there will likely continue to be many older HIV-infected children in the same situation as those described in this follow-up study. They will not have been recognized as being HIV-infected. It is important that such chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
106
4
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 38 publications
7
106
4
2
Order By: Relevance
“…Contrary to Msellati et al (1993) reporting cognitive delays in their Rwandan infants, Bagenda et al (2006) found no significant cognitive or neurological differences between HIV-infected and uninfected children in Uganda. The study by Bagenda and colleagues (2006) recruited the same children from the study by Drotar et al (1997) who had reached school-age to assess cognitive development (Abubakar, et al, 2008).…”
Section: )?contrasting
confidence: 86%
See 1 more Smart Citation
“…Contrary to Msellati et al (1993) reporting cognitive delays in their Rwandan infants, Bagenda et al (2006) found no significant cognitive or neurological differences between HIV-infected and uninfected children in Uganda. The study by Bagenda and colleagues (2006) recruited the same children from the study by Drotar et al (1997) who had reached school-age to assess cognitive development (Abubakar, et al, 2008).…”
Section: )?contrasting
confidence: 86%
“…A possible explanation for the discrepancies between these studies is that children from the first Ugandan study (Drotar, et al, 1997) did not have access to ART. Therefore this study (Bagenda, et al, 2006) may be confounded by survival bias where children with more severe impairments would have died before reaching school-age.…”
Section: )?mentioning
confidence: 99%
“…This difference is likely due to the poor development of the immune system in children 5 . The diagnosis of AIDS in children is a challenge because the clinical manifestations resemble many other common childhood illnesses, including prolonged or recurrent fever, chronic or recurrent diarrhea, generalized lymphadenopathy, persistent or chronic cough, repetitive upper respiratory tract infections including sinusitis and otitis, recurrent pneumonia, persistent oral candidiasis, ponderal-stature deficit, skin lesions especially eczema, hepatosplenomegaly and delayed neuropsycomotor development 6 .…”
mentioning
confidence: 99%
“…1 Diagnosis in children is a challenge, as the clinical presentations are similar to other diseases common in childhood. 2 Early diagnosis of HIV infection, in children identified as having been exposed to the virus, as well as in those that have nonspecific constitutional symptoms, demanding recurrent medical attention, will determine the prognosis of these children.…”
mentioning
confidence: 99%